Cross-Sectional Age Differences in Canine Personality Traits; Influence of Breed, Sex, Previous Trauma, and Dog Obedience Tasks - Wallis, Lisa J.; Szabó, Dóra; Kubinyi, Enikő (Frontiers in Veterinary Science, 2020)
The dog has been suggested as a possible model for personality development over the lifespan, however, we know little about how ageing may shape their personality or the magnitude of age-related changes. Previously we established that ageing influences multiple dog demographics, which could also affect how personality traits change across different age periods. A demographic questionnaire and the Dog Personality Questionnaire were completed for a cross-sectional sample of 1207 adult dogs living in Hungary (Mage = 7.71, SD = 4.12), split into six different age groups. Results revealed three of the five factors showed significant age effects. Activity/Excitability decreased with age, and whilst Responsiveness to training also decreased, only dogs older than 12 years differed significantly from the other groups. Aggressiveness towards animals showed a quadratic trajectory peaking in dogs aged 6 to 10 years. The greatest magnitude of age-related change was detected between late senior and geriatric ages, likely caused by compensatory behavioural changes to biological ageing and owner attitudes to ageing. When the models were re-run including the other explanatory variables, age group was no longer significant for the Responsiveness to training trait. The amount of time spent interacting/playing with the owner partially mediated the relationship between age and this trait, implying that interventions to increase play and training motivation may alleviate the negative effects of ageing on dogs’ trainability. 15 out of 28 explanatory variables were significantly associated with at least one of the five factors (weight, breed (pure/mixed breed), sex, off-leash activity, diet, previous trauma, age of dog when arrived in the household, play, dog training activities, number of known commands and dog obedience tasks). Similarly to humans, dogs that had previously experienced trauma scored higher in fearfulness and aggression. A higher level of basic obedience was linked to some desirable dog personality traits (lower Fearfulness and Aggression, and higher Activity/Excitability and Responsiveness to training). Regardless of the direction of this relationship, obedience is an important aspect contributing to dog personality questionnaires and the dog-owner relationship. This study is unique in that it considered a wide variety of demographic variables which are influenced by ageing.